Social Identity of Blindness and Its Impact on Well-Being During the Pandemic - Kocabag, Dolunay (Revue YOUR Review (York Online Undergraduate Research), 2022)
The present study explored the social identity of Canadians with sight loss in the context of the Covid-19 pandemic. The goal of the study was to determine if measures of sight loss can predict social identity described by three factors: group centrality, group affect, and in group ties. Bivariate correlations indicated that age of onset of the sight loss, severity of sight loss, and activity impairment due to sight loss did not predict the strength of identification with the sight loss community. However, an individual’s acceptance of their sight loss and their openness to share experiences related to sight loss significantly correlate with the strength of their identification with the Canadian sight loss community. The second goal of the study was to determine if sight loss social identity can play a role in the well-being of individuals with sight loss during the Covid-19 pandemic. Bivariate correlations showed that stronger identification with the sight loss community predicted lower levels of Covid-19 related stress for three factors of social identity.